2020
DOI: 10.2217/bmm-2019-0176
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Characteristics and Biomarkers of Early-Stage Heart Failure

Abstract: Aim: We aimed to identify metabolic characteristics of early-stage heart failure (HF) and related biomarkers. Patients & methods: One hundred and forty-three patients with New York Heart Association class I–IV HF and 34 healthy controls were recruited. Serum metabolic characteristics of class I HF were analyzed and compared with those of class II–IV HF. Potential biomarkers of class I HF with normal N-terminal-pro-B-type natriuretic peptide (NT-proBNP) level were screened and validated in additional 72 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…There is a significant and growing body of literature where metabolomic analyses have been performed in adult HF subjects [27][28][29][30]. To our knowledge, there exist only two reports of metabolomic analyses of the myocardium of SV subjects, including one in adult non-failing SV patients with a systemic LV [18,19] and one in young SVNF and SVHF patients with a systemic RV [20].…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant and growing body of literature where metabolomic analyses have been performed in adult HF subjects [27][28][29][30]. To our knowledge, there exist only two reports of metabolomic analyses of the myocardium of SV subjects, including one in adult non-failing SV patients with a systemic LV [18,19] and one in young SVNF and SVHF patients with a systemic RV [20].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the further study of multi-omics technologies, researchers have found that the ultimate effect of gene or protein regulatory action was to cause changes in metabolites in body ( Holmes et al, 2018 ; Yang et al, 2018 ; Zhang et al, 2022 ). Metabolomics studied endogenous small molecule compounds at the end of metabolic pathways, which could skip the complex regulatory processes of body and directly reflect the final physiological and pathological changes ( Ke et al, 2018 ; Guo et al, 2020 ; Chumachenko et al, 2022 ). Through the analysis of differential metabolites, researchers could reveal pathogenic mechanisms, confirm diagnostic biomarkers, estimate disease risk, and monitor treatment processes ( Wishart, 2019 ; Shin et al, 2020 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%